THE VERTEBRAL COLUMN OF THE TRIASSIC FISH SAURICHTHYS (ACTINOPTERYGII) AND ITS STRATIGRAPHICAL SIGNIFICANCE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The Norian beds of the Southern Calcareous Alps have yielded at least four species belonging to Saurichthys. Their vertebral column has large praezygapophyses, which, in each of these nominai species, attain a different relative length. The latter is inversely proportional to age: in fact, the youngest two, coeval species have the longest praezygapophyses, at least six times as long as a vertebral segment. Such a conspicuous change in an otherwise conservative genus, is here relateci to a major ichthyofaunal break that saw the florishing of the Pholidophoridae. The relative length of the praezygapophyses can be a very useful stratigraphical means, at least in the Norian (Upper Triassic).
Keywords: Triassic; Saurichthys (Actinopterygii); Vertebral column; Stratigraphy.